Blue Economy and Corporate Value Creation: A Bibliometric Analysis of Global Research Trends - Kuncoro, Fajar Dwi; Salisa , Meilenia Rahma; Rahmatika , Armizha; Sari, Nur Afiqoh; Setiawan , Mochammad Charis (LifeSciFi, 2025)
The blue economy has emerged as a key strategy for sustainable development. This study employs a bibliometric approach to analyze the development and research trends of the blue economy, specifically its relationship with economic performance and firm value. Conceptualized as a sustainable development strategy, the blue economy integrates economic, social, and environmental dimensions centered on marine and coastal resources. Data from the Scopus database (2010-2025) was analyzed using VOSviewer software to map collaboration networks and thematic evolution. The results reveal a substantial increase in publications since 2016, peaking in 2024, highlighting the topic’s growing global relevance. China is the dominant contributor, led by institutions like the Ocean University of China and the Ministry of Natural Resources, followed by universities from the UK, the Netherlands, Australia, and Canada. The analysis identified three primary research clusters, sustainability, marine aspects, and economic and social sectors within the blue economy. The study confirms the blue economy’s significant contribution to economic growth, resource efficiency, and social welfare. However, its success is contingent upon effective governance, technological innovation, and strong integration between the public and private sectors, outlining critical areas for future development and policy focus.